Cortical Development Neural Diversity and Neocortical Organization - Kageyama, Ryoichiro; Yamamori, Tetsuo (Springer Japan : Imprint: Springer, 2013)
This book reviews recent progress in cortical development research, focusing on the mechanisms of neural stem cell regulation, neuronal diversity and connectivity formation, and neocortical organization. Development of the cerebral cortex, the center for higher brain functions such as cognition, memory, and decision making, is one of the major targets of current research. The cerebral cortex is divided into many areas, including motor, sensory, and visual cortices, each of which consists of six layers containing a variety of neurons with different activities and connections. As this book explains, such diversity in neuronal types and connections is generated at various levels. First, neural stem cells change their competency over time, giving sequential rise to distinct types of neurons and glial cells: initially deep layer neurons, then superficial layer neurons, and lastly astrocytes. The activities and connections of neurons are further modulated via interactions with other brain regions, such as the thalamocortical circuit, and via input from the environment. This book on cortical development is essential reading for students, postdocs, and neurobiologists.